Assessing travel time and transportation costs in sub-Saharan Africa: A case study in Malawi - Guo, Zhe; Hawkins, James (International Food Policy Research Institute, 2016)
The government of Malawi is pursuing an export led agricultural growth strategy, and therefore improving transport quality between major urban areas, as well as between rural areas and ports of trade or market centers, is a key pri-ority (DTIS, 2014). For this reason, being able to assess travel distances, times, and costs for major commerce routes is an important first step. Despite this, there exists a lack of basic data relating to the geographic and economic as-pects of road travel in many of these countries. The purpose of this technical brief is to describe the procedure taken for the estimation of transportation costs for use in the development of a spatially disaggregated, market level model of the Malawian agricultural sector, which is being done as part of BioSight’s ongoing work on the sustainable intensi-fication of agriculture in Africa, south of the Sahara. Modelling exercises such as these require estimation of the mar-keting margins of agricultural inputs and outputs traded across regions. The transport cost makes up a significant component of the marketing margin. High quality data on transport costs is therefore crucial for the parameterization and application of market models such as these. This technical brief describes a procedure for estimating transport distances, times, and costs between three major urban areas in south, central, and north Malawi. The difficulties around obtaining reliable spatial data and how to use these to develop and assess specific transport routes are dis-cussed.